Malawi : Poverty Reduction Strategy Paper; Annual Progress Report. (IMF Staff Country Reports; Country Report ;, 2006)
This paper reviews the Annual Progress Report on Malawi's Poverty Reduction Strategy (MPRS). The poverty situation remained high over the implementation period of the MPRS. The government continued funding activities that have been perceived to have an impact on poverty reduction. The MPRS outlined a number of macroeconomic policies that have been adhered to achieve the macroeconomic targets. These policies have been mainly in the form of monetary, fiscal, and structural policies.